A sketch-based system for modeling 3D objects: Applications to taxonomy - Ramos, Saulo; Santos, Charles Morphy D.; Sousa, Mario Costa; Gois, João Paulo (Zootaxa, 2021)
We present a sketch-based system for modeling 3D objects with multiple contours as overlaid structures, allowing users to infer perceivable symmetries and occluded parts of the model prior to its automatic 3D reconstruction. Many approaches for sketch-based interfaces and modeling focus on the final drawing and 3D reconstruction of solid objects, exploring, as inputs, contours; however, when the subject consists of multiple drawings as overlaid structures, as usual in species descriptions, these approaches have to roughly infer or discard occluded parts. Unlike previous sketch-based techniques, we explore a set of 2D visual effects to enhance the visual perception of users while sketching multiple overlaid objects in single-view. The proposed system was applied to general simple zoological and botanical sketches as well as to published descriptions of species of Diptera, demonstrating its usefulness for taxonomy.